2017
DOI: 10.1186/s13102-017-0077-x
|View full text |Cite
|
Sign up to set email alerts
|

Towards evidence based strength training: a comparison of muscle forces during deadlifts, goodmornings and split squats

Abstract: BackgroundTo ensure an efficient and targeted adaptation with low injury risk during strength exercises, knowledge of the participant specific internal loading conditions is essential. The goal of this study was to calculate the lower limb muscles forces during the strength exercises deadlifts, goodmornings and splits squats by means of musculoskeletal simulation.Methods11 participants were assessed performing 10 different variations of split squats by varying the step length as well as the maximal frontal tib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 49 publications
4
24
2
Order By: Relevance
“…High activity levels in these exercises may facilitate training‐induced adaptations in the hamstrings, although adaptations in response to these exercises are unclear. In accordance with previous literature, particularly low overall hamstrings activity was observed in GM, which is apparently associated with low hamstring muscle forces in this exercise . Exercises inducing limited hamstrings activity are likely suboptimal to facilitate meaningful muscle adaptations.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…High activity levels in these exercises may facilitate training‐induced adaptations in the hamstrings, although adaptations in response to these exercises are unclear. In accordance with previous literature, particularly low overall hamstrings activity was observed in GM, which is apparently associated with low hamstring muscle forces in this exercise . Exercises inducing limited hamstrings activity are likely suboptimal to facilitate meaningful muscle adaptations.…”
Section: Discussionsupporting
confidence: 90%
“…In accordance with previous literature, 28 particularly low overall hamstrings activity was observed in GM, which is apparently associated with low hamstring muscle forces in this exercise. 29 Exercises inducing limited hamstrings activity are likely suboptimal to facilitate meaningful muscle adaptations. The relevance of the relative roles of individual hamstring muscles in hamstring injury is yet to be clarified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the capacity of musculoskeletal models to predict KCFs during other activities has been less thoroughly studied. 37,43 Furthermore, because musculoskeletal models have previously struggled to predict absolute measures of joint loading, they are often used instead to predict differences in metrics between e.g., subjects, groups of subjects, activities, or pathologies. However, due to the limited number of subjects and activities in the publicly available benchmark validation datasets, the ability to establish differences has not been extensively validated.…”
Section: Introductionmentioning
confidence: 99%
“…The body drag, especially how it was performed in this study (Peace Officer Standards and Training, 2012;Lockie et al, 2018b;Lockie et al, 2019b;Lockie et al, 2019e;Moreno et al, 2019), has some similarities to a deadlift. In an analysis of lower-body strength exercises, Schellenberg, Taylor, & Lorenzetti (2017) found that the quadriceps were most active in the deadlift. The need to physically stand with the dummy by extending the legs could have increased the QUAD TL.…”
Section: Discussionmentioning
confidence: 99%